Rodzina o zmienionej strukturze wewnętrznej jako źródło wykluczenia społecznego młodzieży = Family with the modified internal structure as the source of social exclusion of the youth - Sendyk, Marzena; Ilnicka, Renata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
A family with the modified internal structure creates different life conditions for an adolescent from the conditions in full families. The research run on the junior high school students proves that the families suffer from difficulties more often - the difficulties connected both with the sphere of material existence and the sphere of mutual relationships.
Keywords: wykluczenie społeczne; młodzież gimnazjalna; rodzina niepełna; trudności wychowawcze; depresja dzieci i młodzieży; zachowania agresywne